Exploring the Reasons of Aggressive Teacher Behavior Affecting Learners’ Competencies At K-12: An Empirical Analysis - Syed Ghazanfer Abbas; Muhammad Ehsan; Anwar ul Haq (Jurnal Multidisiplin Madani, 2023)
Good behaviour is a prerequisite for both teaching and learning and is a fundamental educational outcome that society should demand. They will become more impatient and uneducated if we do not provide the good order and good results that society expects from instructors. The main purpose of this study was to explore the reasons of aggressive behavior of educators. The objective of the study was: To explore the reasons that affects the competencies of learners due to aggressive behavior of teachers at K-12. Population of the study consisted of all students (621) during the year 2020-2021 from the Federal Government Boys School & Colleges, Rawalpindi. Random sampling technique was used in the selection of sample. Self-structured Questionnaire was used as a research tool with five-point Likert Scale. The major findings of the study were: Teachers were suffering from psychological problems. They also face domestic problems in their life. In the process of teaching teachers do not have command on their subjects. Teachers are not skilled in conveying their subject matter to students. Teachers were prone to social indiscipline. It was conclude that teachers are suffering from financial problems. Teachers are forced to adopt such behavior due to the pressure of office affairs. Due to students’ low performance in their studies, teachers get aggressive